The MCP-1 A-2518G polymorphism increases the risk of Alzheimer's disease: A case-control study. (1st April 2021) - Xu, Lifei; Dong, Qiuping; Xu, Liben; Zou, Wei; Li, Hui
Highlights: MCP-1 A-2518 G polymorphism correlates with an elevated risk of AD. MCP-1 A-2518 G polymorphism correlates with the increased MCP-1 serum levels. The interaction between MCP-1 A-2518 G polymorphism and smoking contributes to increased risk of AD. Abstract: Monocyte chemoattractant protein-1 (MCP-1) is reported to associate with the severity and development of Alzheimer's disease (AD). While a few studies have examined the association between the MCP-1 A-2518 G polymorphism and AD risk, no Chinese study has undertaken a study of this association. Therefore, a case-control study with 212 AD cases and 268 controls was designed in Chinese participants. Logistic regression analysis was utilized to probe the potential link between AD susceptibility and the MCP-1 A-2518 G polymorphism. We observed that the GG or GG + AG genotype was shown to elevate the risk of AD. Subgroup analysis revealed this increased risk effect was also presented in males, smokers, APOE ε4+ and those participants ≥ 65 years old. Notably, cross-over analysis found that this polymorphism interacted with smoking, contributing to the increased risk of AD. In addition, we found that the serum MCP-1 levels of AD patients were evidently higher than in controls. Furthermore, the MCP-1 A-2518 G polymorphism was linked with the serum MCP-1 levels of AD patients, but not controls. In conclusion, the MCP-1 A-2518 G polymorphism correlates with an elevated risk of AD and increased MCP-1 serum levels. The interaction between the MCP-1 A-2518 G polymorphism and smoking contributes to the increased risk for AD in Chinese Han individuals.